Population structure and gene flow of the Brazilian shrub Helicteres brevispira - Franceschinelli, E.V; Kesseli, R (Heredity, 1999)
Helicteres brevispira is a pioneer species of the tropical riparian forest whose populations appear to cycle through episodes of extinction and recolonization. Therefore, genetic consequences of founding events may strongly affect the genetic structure of its populations. An analysis of F-statistics showed that the studied population of H. brevispira is genetically substructured with the highest values of F(ST) found in areas of high plant densities. Spatial autocorrelation analysis showed that genetic patches have diameters of 3-6 m. Although pollinator movements are usually between plants which are 3-6 m apart, longer flights occur and the neighbourhood area is estimated to have a diameter of 15 m. This suggests that genetic patches are smaller than the neighbourhood area. Seed dispersal is limited, mostly less than 2 m from the mother plants. Thus, short seed dispersal, seed dormancy and founder effects in the seed bank may be the most important determinants of genetic structure in populations of H. brevispira. Factors such as drift and inbreeding may also increase the level of substructure in this population, but the equilibrium model of isolation by distance does not fit our data.